Peningkatan Keaktifan Belajar Peserta Didik Melalui Model Pembelajaran Berbasis Proyek Pada Pembelajaran Tematik Di Kelas IV SDN 8 Mataram - Anggun Kamilasari; Elisa Fatmawati; Nurul Aini; Darmiany Darmiany (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
The purpose of this study is to increase student engagement through the use of project-based learning (PJBL) model. This type of study is a classroom study. The method of data collection is through the use of observation sheets and questionnaires. The subjects of the study were class IV students of SDN 8 Mataram. There were a total of 27 class IV students, of which 12 were male students and 15 were female students. The results of the study indicate an increase in students' learning activity. The results of observations of students' educational activity showed that in the pre-course cycle, student activity was only 52%, then increased to 59% in the first cycle and increased again to 70% in the second cycle. Then the results of a survey of the student’s educational activities also showed a similar increase. The results of the pre-course analysis showed that the educational activity of students was 59%, then increased to 68% in the first cycle and increased again in the second cycle to 74%.